Efeito da temperatura ambiente e da restrição alimentar protéica ou energética sobre o ganho de peso e crescimento ósseo de frangos de corte - Pelicano, E. R. L.; Bernal, F. E. M.; Furlan, R. L.; Malheiros, E. B.; Macari, Marcos [UNESP] (FapUNIFESP (SciELO), 2005)
The effect of protein or energy restriction during the second week post-hatching on body weight gain and femur development of broiler chickens reared at different environmental temperatures (18°C, 25°C and 33°C) was studied. From 1 to 7 days of age and after a restriction period broilers were fed on a control diet with 2850 kcal ME/kg and 20% crude protein. From 8 to 14 days of age, two groups of broilers were fed on restricted energy and protein diets with 2565kcal ME/kg and 20% of crude protein or 2850kcal ME/kg and 15% of crude protein, respectively. At 14, 21, 28, 35 and 42 days, the bones were weighed and the length and width of bones measured. The protein restriction reduced the body weight gain and the diameter of bone at second week of life. After 21 days of age no differences between treatments for these traits were observed. The body weight gain and femur growth were not affected by energy restriction. The high temperature (33°C) reduced weight gain and femur diameter from 21 to 42 days of age, and femur length at 42 days of age. The protein restriction at second week or the high environmental temperature after 21 st day of life decreased body weight gain and femur growth of broiler chickens.
Effect of environmental temperature and protein or energy restriction on body weight gain and broiler chicken bone growth
Keywords: Bone growth; Broiler chick; Feed restriction; Temperature; Gallus gallus